Length‐weight relationships of 58 fish species in French Guiana streams. (14th March 2015) - Allard, L.; Toussaint, A.; Vigouroux, R.; Brosse, S.
Summary: Length‐weight relationship parameters of the form W = aL b are presented for 58 fish species representing 36 genus and 19 families captured in streams of French Guiana. LWRs for 53 of the species are estimated for the first time.